MASSETERIC ELECTROMYOGRAPHIC SILENT PERIOD DURATION IN PATIENTS WITH TEMPOROMANDIBULAR-JOINT DYSFUNCTION - Trindade, A. S.; Westphalen, F. H.; Trindade, IEK; Maringoni, R. L.; Atta, A. G. (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
1. The present study compared the duration of the electromyographic silent period (SP) of the masseter muscles elicited by chin-tapping in normal asymptomatic adults (N = 39) and in a group with symptoms of temporomandibular joint dysfunction (TMJD) (N = 31).2. EMG activity was recorded from right (RM) and left (LM) masseter muscles using bipolar surface electrodes coupled to a DISA 1500 EMG-System. During maximal clenching, ten taps were applied downwards to the chin with a reflex hammer.3. The mean SP durations obtained for the normal group were 25.45 +/- 4.20 ms (RM) and 25.33 +/- 4.18 ms (LM), whereas the TMJD group presented significantly greater values (P < 0.01, Student t-test) of 41.89 +/- 12.94 ms (RM) and 42.40 +/- 12.99 ms (LM). The upper limits of normality calculated for RM and LM were 32.36 ms and 31.21 ms, respectively. Eighty-four percent of patients with TMJD showed SP durations above these limits.4. The results indicate that the measurement of masseteric SP duration may be used as an objective diagnostic method of TMJ disorders, provided that borderline values are interpreted with caution along with clinical impressions.
Keywords: ELECTROMYOGRAPHY; SILENT PERIOD; TEMPOROMANDIBULAR JOINT DYSFUNCTION